Answer:
[tex]\frac{d y}{d x} = - (2 x + 3 x^{2} )sin2(x^{2} +x^{3})[/tex]
Step-by-step explanation:
Step(i):-
Given y = cos² (x² + x³) ....(i)
By using differentiation formulas
a) [tex]\frac{d}{dx} (cosx) = -sinx[/tex]
b) [tex]\frac{d}{dx} (x^{n} ) = n x ^{n-1}[/tex]
Step(ii):-
Differentiating equation (i) with respective to 'x'
First apply formula [tex]\frac{d}{dx} (x^{n} ) = n x ^{n-1}[/tex]
[tex]\frac{d y}{d x} = 2 cos (x^{2} +x^{3} )^{2-1} \frac{d}{d x} (cos(x^{2} +x^{3})[/tex]
Now we will apply formula
[tex]\frac{d}{dx} (cosx) = -sinx[/tex]
[tex]\frac{d y}{d x} = 2 cos (x^{2} +x^{3} ) (-sin(x^{2} +x^{3})\frac{d}{dx} (x^{2} +x^{3} )[/tex]
Again apply formula [tex]\frac{d}{dx} (x^{n} ) = n x ^{n-1}[/tex]
[tex]\frac{d y}{d x} = 2 cos (x^{2} +x^{3} ) (-sin(x^{2} +x^{3}) (2 x + 3 x^{2} )[/tex]
[tex]\frac{d y}{d x} = -2 sin (x^{2} +x^{3} ) cos(x^{2} +x^{3}) (2 x + 3 x^{2} )[/tex]
we know that trigonometric formulas
Sin 2θ = 2 sinθ cosθ
[tex]\frac{d y}{d x} = -sin2(x^{2} +x^{3}) (2 x + 3 x^{2} )[/tex]
Final answer:-
[tex]\frac{d y}{d x} = - (2 x + 3 x^{2} )sin2(x^{2} +x^{3})[/tex]